Autobiography of a wound - Rebele-Henry, Brynne, 1999- (Pitt poetry series., 2018)
In ancient fertility carvings, artists would drill holes into the woman's body to signify penetrability, which is the basis of Autobiography of a Wound: allowing those wounds and puncture marks to speak through the fertility figures. The wounds are chronicled through letters and poems addressed to F (F stands for the fertility carvings themselves, which are being addressed as one unified deity), and A (Aphrodite, who is being referenced as a general deity of womanhood, a figurine that reappears throughout the poems, and a symbol that is referenced or portrayed in almost every fertility figurine or carving). Autobiography of a Wound reconstructs the narrative surrounding female pathos and the idea of the hysteric girl.